2022
DOI: 10.1002/est2.340
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance and mold discoloration of thermally modified wood containing bio‐based phase change material for heat storage

Abstract: The work presents the results of thermal performance and mold discoloration of thermally modified wood‐based composites incorporating multicomponent fatty acids as a bio‐based phase change materials (BPCM). Thermally modified Scots pine (TMP), beech (TMB), and spruce (TMS) sapwood were impregnated with a multicomponent mixture of linoleic acid and coconut oil fatty acids at a ratio of 20:80. Samples with different BPCM uptakes were analyzed in the temperature range typical for building indoor conditions. Leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Moreover, mold growth was directly related to moisture and temperature levels. Similarly, Nazari et al (2022a) evaluated the thermal behavior and the potential susceptibility to mold-induced discoloration of three thermally enhanced wood species (Scots pine, beech, and spruce) containing a blend of coconut oil and linoleic acid as PCM. The incorporation of PCM into wood samples resulted in significant thermal mass improvements, especially in Scots pine, which presented the highest latent heat of 70 J/g.…”
Section: Effect Of Impregnated Pcm On Wood Durabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mold growth was directly related to moisture and temperature levels. Similarly, Nazari et al (2022a) evaluated the thermal behavior and the potential susceptibility to mold-induced discoloration of three thermally enhanced wood species (Scots pine, beech, and spruce) containing a blend of coconut oil and linoleic acid as PCM. The incorporation of PCM into wood samples resulted in significant thermal mass improvements, especially in Scots pine, which presented the highest latent heat of 70 J/g.…”
Section: Effect Of Impregnated Pcm On Wood Durabilitymentioning
confidence: 99%
“…There have been few studies that have explored the use of wood for PCM integration. Wood is a renewable resource and the integration of PCMs into its structure could lead to the elaboration of bio-based materials for construction purposes (Nazari et al 2020). To be more specific, there is no published research on the incorporation of PCMs into wood-based panels such as oriented strand boards, fiberboards, or particleboards.…”
Section: Introductionmentioning
confidence: 99%
“…14 Impregnation of BPCMs into wood has gained attention in recent years due to the excellent properties of wood as a building material, including its mechanical strength, low thermal conductivity, sustainability, and low density. [15][16][17] Due to the low density and high strength of wood, timber buildings have low total thermal mass. Phase-change materials in wood composites with working temperatures of 18 C to 25 C can absorb extra heat and release it when the temperature falls below a certain comfort point.…”
Section: Introductionmentioning
confidence: 99%
“…Beech and thermally modified beech (TMB) are increasingly used in European countries and is being implemented more and more in the construction sector. In the previous studies, 17,29 it was showed a possibility of impregnation of beech and TMB with BPCM based on coconut oil fatty acids. The highest latent heat of this BPCMs without wood was 122 J/g.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, solid wood impregnated with BPCM has been the topic of a number of studies considering different wood species and thermally treated wood. The studies [10,11] showed that solid wood impregnated with BPCM has higher thermal mass compared to non-impregnated wood and can serve as energy smart material for building applications. The studies revealed that leakage of the BPCM is a serious obstacle regarding incorporation of BPCMs in solid wood.…”
Section: Introductionmentioning
confidence: 99%